2023
DOI: 10.3390/jcm12113695
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Subphenotypes in ARDS: Diagnostic and Therapeutic Implications and Overlap with Other ARDS Subphenotypes

Abstract: Acute respiratory distress syndrome (ARDS) is a highly heterogeneous clinical condition. Shock is a poor prognostic sign in ARDS, and heterogeneity in its pathophysiology may be a barrier to its effective treatment. Although right ventricular dysfunction is commonly implicated, there is no consensus definition for its diagnosis, and left ventricular function is neglected. There is a need to identify the homogenous subgroups within ARDS, that have a similar pathobiology, which can then be treated with targeted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 100 publications
(193 reference statements)
0
2
0
Order By: Relevance
“…Most recently, Chotalia et al [ 61 ] have utilized LCA to identify novel cardiovascular subphenotypes in ARDS. They combined transthoracic echo and clinical variables from more than 1,000 patients who were diagnosed with ARDS.…”
Section: Unbiased Approaches To Ards Subphenotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, Chotalia et al [ 61 ] have utilized LCA to identify novel cardiovascular subphenotypes in ARDS. They combined transthoracic echo and clinical variables from more than 1,000 patients who were diagnosed with ARDS.…”
Section: Unbiased Approaches To Ards Subphenotypesmentioning
confidence: 99%
“…This hyperdynamic subphenotype has a 59% mortality and does independently predict an increased risk of death. Chotalia et al [ 61 ] established a parsimonious model to divide patients into these distinct subphenotypes using parameters available by bedside transthoracic echocardiogram and found that measures of RV systolic dysfunction and cardiac index can accurately discriminate the subphenotypes.…”
Section: Unbiased Approaches To Ards Subphenotypesmentioning
confidence: 99%